Penyuluhan Hukum : Pencegahan Kenakalan Remaja Di Desa Ngujung Kecamatan Maospati Kabupaten Magetan - Moch Juli Pudjiono; Bambang Sukarjono; Hery Sumanto (JURNAL DAYA-MAS, 2020)
This service aims to provide an understanding of juvenile delinquency problems. By using legal counseling methods. Location of community service in Ngujung Village, Maospati Subdistrict, Magetan District. Based on the results of the discussion show that adolescence is a period where an individual experiences a transition from one stage to the next and experiences changes in both emotions, body, interests, behavioral patterns, and also full of problems. While Juvenile delinquency (juvenile delinquency) is malicious behavior, or crime / delinquency of young people is a social pathology in children and adolescents caused by a form of social neglect, so they develop deviant forms of behavior. For this reason, efforts to prevent juvenile delinquency can be done, among others: (1) Parents must pay more attention, supervision, and affection to children and parents must open two-way communication (listening and open) to children, (2) Giving limits on freedom, (3) Providing religious education to adolescents, (4) Teaching adolescents not to be easily influenced by negative relationships, (5) Providing positive activities to adolescents so that adolescents are busy and do not have time to do things negative things and (6) Providing knowledge about laws that regulate juvenile delinquency and sanctions.Â Keywordsâ€”: Extension of Law; Juvenile Delinquency.